Doxorubicin-loaded cholic acid-polyethyleneimine micelles for targeted delivery of antitumor drugs: synthesis, characterization, and evaluation of their in vitro cytotoxicity - Amjad, Muhammad Wahab (Springer, 2012)
Doxorubicin-loaded micelles were prepared from a copolymer comprising cholic acid (CA) and polyethyleneimine (PEI) for the delivery of antitumor drugs. The CA-PEI copolymer was synthesized via pairing mediated by N,N’-dicyclohexylcarbodiimide and N-hydroxysuccinimide using dichloromethane as a solvent. Fourier transform infrared and nuclear magnetic resonance analyses were performed to verify the formation of an amide linkage between CA and PEI and doxorubicin localization into the copolymer. Dynamic light scattering and transmission electron microscopy studies revealed that the copolymer could self-assemble into micelles with a spherical morphology and an average diameter of <200 nm. The CA-PEI copolymer was also characterized by X-ray diffraction and differential scanning calorimetry. Doxorubicin-loaded micelles were prepared by dialysis method. A drug release study showed reduced drug release with escalating drug content. In a cytotoxicity assay using human colorectal adenocarcinoma (DLD-1) cells, the doxorubicin-loaded CA-PEI micelles exhibited better antitumor activity than that shown by doxorubicin. This is the first study on CA-PEI micelles as doxorubicin carriers, and this study demonstrated that they are promising candidates as carriers for sustained targeted antitumor drug delivery system.